Penguatan Literasi Membaca melalui Model LOK-R pada Siswa SDIT Al Hambra Pesawaran - Muhammad Singgih; Atika Nur Hidayati; Nita Septiani (STIT Darul Fattah Bandar Lampung, 2024)
Literacy is one of the main foundations that must be taught at the elementary school level. If the literacy foundation is strong since elementary school, students will adapt more quickly to learning. The lack of literacy culture in today's children and youth environment needs to be recognized. This encouraged the team to carry out PkM with the title PkM